2021
DOI: 10.1186/s13765-021-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

Duckweeds: their utilization, metabolites and cultivation

Abstract: Duckweeds are floating plants of the family Lemnaceae, comprising 5 genera and 36 species. They typically live in ponds or lakes and are found worldwide, except the polar regions. There are two duckweed subfamilies—namely Lemnoidea and Wolffioideae, with 15 and 21 species, respectively. Additionally, they have characteristic reproduction methods. Several metabolites have also been reported in various duckweeds. Duckweeds have a wide range of adaptive capabilities and are particularly suitable for experiments r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 141 publications
(237 reference statements)
0
26
0
Order By: Relevance
“…The vitexin and apigenin in duckweed have been suggested as constituents for treating non-small lung cancer [55] and as anticancer adjuvants, and flavone C-glycosides from L. japonica exhibits cytotoxic activity against various human cancer cell lines (HepG-2, SW-620, A-549) [87]. In particular, L. minor flavonoids have immunosuppressive effects by reducing free hemoglobin content and antibody production in human whole blood [87]. Moreover, fruit and vegetable consumption rich in polyphenolic substances and iron chelating agents prevent cancer by ROS scavenging [85].…”
Section: Discussionmentioning
confidence: 99%
“…The vitexin and apigenin in duckweed have been suggested as constituents for treating non-small lung cancer [55] and as anticancer adjuvants, and flavone C-glycosides from L. japonica exhibits cytotoxic activity against various human cancer cell lines (HepG-2, SW-620, A-549) [87]. In particular, L. minor flavonoids have immunosuppressive effects by reducing free hemoglobin content and antibody production in human whole blood [87]. Moreover, fruit and vegetable consumption rich in polyphenolic substances and iron chelating agents prevent cancer by ROS scavenging [85].…”
Section: Discussionmentioning
confidence: 99%
“…All nine essential amino acids are also found in this plant [11]. Previous studies have revealed the presence of 20-35% protein, 4-7% fat, and 4-10% starch in plants from Lemnaceae, and W. globosa has been used as a protein source in animal feed and as a raw material for many industrial products including bioalcohol and biodegradable plastics [12,13].…”
Section: Introductionmentioning
confidence: 88%
“… 25 Duckweeds contain a variety of secondary metabolites, including phenolic compounds (favonoids, phenylpropanoids, and tannins) and terpenoids. 26 L. punctata is known to have a higher favonoid content, such as apigenin, luteolin, vitexin, orientin and its derivatives, which have a variety of bioativities. 27 , 28 Among them, the compound luteolin has been identified to inhibit the growth of M. aeruginosa remarkably with IC 50 6.5 mg/L.…”
Section: Discussionmentioning
confidence: 99%